Impact of lupus nephritis on foeto-maternal outcomes: a retrospective case-control study - shahwar, dur-e-; Rehmani, Duriya; Amir Raza; Malik, Ayesha (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the impact of lupus nephritis on foeto-maternal outcomes in patients with systemic lupus erythematosus, and to compare it with those without lupus nephritis. Method: The retrospective, case-control study was conducted from June to December 2023 at Aga Khan University Hospital, Karachi, and comprised data of pregnant patients with systemic lupus erythematosus from January 1998 to December 2019. Patients with biopsy-confirmed lupus nephritis were placed in group A, while those without lupus nephritis were placed in control group B. Maternal and perinatal outcomes were compared between the groups. Data was analysed using SPSS 19. Results: Of the 125 women, 49(39.2%) were in group A with mean age 30.33±4.34 years, and 76(60.8%) were in group B with mean age 29.87±4.06 years (p>0.5). Antenatal flare-ups occurred in 17(34.7%) group A patients during the third trimester compared to 13(17.1%) in group B. The rate of pre-eclampsia and eclampsia were significantly higher in group A women compared to group B women (p<0.05). Premature births were seen more often in group A (p<0.05). Conclusion: Third-trimester flare-ups were seen more often among pregnant women with lupus nephritis, and they were more likely to have pre-eclampsia/eclampsia and preterm birth. Key Words: Pre-eclampsia, Eclampsia, Premature birth, foetal growth retardation, Lupus nephritis, Lupus erythematosus, Systemic.